Epidemiological profile of patients with conjunctival malignancy based on the data on patients presenting to SI “The Filatov Institute of Eye Diseases and Tissue Therapy of the NAMS of Ukraine” Authors - I. O. Safronenkova (Journal of Ophthalmology)
Purpose: To evaluate the incidence and assess the clinical features of conjunctival melanoma and carcinoma based on the data on patients presenting to the Ocular Oncology Department, SI “The Filatov Institute of Eye Diseases and Tissue Therapy of the NAMS of Ukraine". Material and Methods: Medical records of 125 patients with conjunctival malignancy (94 conjunctival melanoma (CM) patients (75.2%) and 31 conjunctival carcinoma (CM) patients (24.8%)) treated at the Filatov Institute in 2004-2024 were retrospectively reviewed. Of these CM patients, 49 (52.1%) were males (age range, 18 to 88 years; median, 51.1 years), and 45 (47.9%) were females (age range, 26 to 87 years; median, 56.6 years). Of these CC patients, 24 (77.4%) were males (age range, 28 to 82 years; median, 64.6 years), and 7 (22.6%) were females (age range, 36 to 77 years; median, 56.6 years). Results: CM and CC were seen in 1.9%-3.4% and 0.5%-1.2%, respectively, of total annual patients presenting with ocular malignancy to the institute. The most common age group among CM patients was 40-59 years (р = 0.02), and among CC patients, 60-79 years (р = 0.01). Most CM patients (57 patients or 60.9%) lived in urban areas (χ2 = 7.7, р = 0.01), and most CC patients (17 patients or 56.3%) lived in rural areas. Primary tumors were seen in 84 CM patients (89.4%) and 22 CC patients (75.8%), and iatrogenic tumors, in 10 CM patients (10.6%) and 7 CC patients (22.5%). Most commonly, iatrogenic lesions were seen after surgical treatment (60% for CM and 83.3% for CC). The most common melanoma anatomic conjunctival location was inner inferior region (34 patients or 36.2%; р = 0.03). The two most common carcinoma anatomic conjunctival locations were outer inferior region (32.8%; р = 0.004) and inner inferior region (25.8%; р = 0.01). Disease duration at presentation was less than 12 months for most (60.7%) CM patients, and less than 3 months for most (72.4%) CC patients (median, 1.4 months). Conclusion: CM and CC were seen in 1.9%-3.4% and 0.5%-1.2%, respectively, of total annual patients presenting with ocular malignancy to the institute. The majority of patients with conjunctival malignancy had CM (60.9%) and the majority (60.9%) of CM patients lived in urban areas. Primary tumors were seen in the majority of patients (89.4% of CM patients and 75.8% of CC patients). Most commonly, iatrogenic lesions were seen after surgical treatment (60% for CM and 83.3% for CC). The outer half of the eye was involved more frequently (50%) in CM patients, and the inner half was involved more frequently (43.8%) in CC patients. Disease duration at presentation was less than 12 months for most CM patients (60.7%), and less than 3 months for most CC patients.